Traditional Chinese Medicine packaging therapy and nursing of a patient with phlebitis caused by peripheral intravenous infusion of anti-tumor Traditional Chinese Medicine (中药封包疗法治疗经外周静脉输注抗肿瘤中药所致静脉炎1例的护理) - LIU Siyuan (刘思源); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠) (中西医结合护理)
To summarized the effect of Traditional Chinese Medicine packaging therapy in the treatment of phlebitis caused by peripheral intravenous infusion of anti-tumor Traditional Chinese Medicine and related nursing measures. Based on the concept of Green treatment of tumor, the Traditional Chinese Medicine packaging therapy, in combination with nursing interventions on psychological health, nutrition and daily living, was carried out to relieve the symptoms of phlebitis. Signs of phlebitis had disappeared, skin temperature returned to normal and pain was relieved after implementation of systematic nursing interventions. The Traditional Chinese Medicine packaging therapy, showing the advantages of Traditional Chinese Medicine external treatment, is safe and effective in treatment of phlebitis caused by peripheral intravenous infusion of anti-tumor drugs. (总结中药封包疗法治疗1例经外周静脉输注抗肿瘤中药所致静脉炎患者的效果。采用肿瘤绿色调护技术中的中药封包疗法, 配合情志、饮食及起居调养。经过系统的护理干预, 患者静脉走向条索状红肿消失, 皮温恢复正常, 硬结消失, 疼痛缓解。中药封包技术属于中医外治技术, 无不良反应, 简单易行, 安全可靠, 能有效缓解抗肿瘤中药静脉输注所致静脉炎。)